2015
DOI: 10.1165/rcmb.2014-0216oc
|View full text |Cite
|
Sign up to set email alerts
|

Coactivator-Associated Arginine Methyltransferase-1 Function in Alveolar Epithelial Senescence and Elastase-Induced Emphysema Susceptibility

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by an irreversible loss of lung function and is one of the most prevalent and severe diseases worldwide. A major feature of COPD is emphysema, which is the progressive loss of alveolar tissue. Coactivator-associated arginine methyltransferase-1 (CARM1) regulates histone methylation and the transcription of genes involved in senescence, proliferation, and differentiation. Complete loss of CARM1 leads to disrupted differentiation and maturation of alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Despite PPE being shown to be cleared from the lungs of rodents within 24 h [37], airspace enlargement continues long after this time [18,36]; indeed we have recently shown emphysema following a single oropharangeal application of PPE to continue progressing to day 161 [19]. Figure 1(A) clearly demonstrates a time-dependent enlargement of the airspaces in H&E-stained lung sections from PPE-treated mice compared with control animals.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Despite PPE being shown to be cleared from the lungs of rodents within 24 h [37], airspace enlargement continues long after this time [18,36]; indeed we have recently shown emphysema following a single oropharangeal application of PPE to continue progressing to day 161 [19]. Figure 1(A) clearly demonstrates a time-dependent enlargement of the airspaces in H&E-stained lung sections from PPE-treated mice compared with control animals.…”
Section: Resultsmentioning
confidence: 90%
“…This may not be the ideal tissue for a biomarker given the difficulties in obtaining biopsies from patients, but it is critical in furthering our understanding of the mechanisms of disease progression. To that end we chose to assess the well-established PPE-induced murine model of emphysema, as it induces airspace enlargement similar to that observed in COPD patients [36], a single treatment leads to progressive disease that is associated with senescence of alveolar epithelial cells [19] and accompanied by increased levels of apoptosis [47]. In the present study, we confirm that a single oropharyngeal application of PPE resulted in a progressive emphysematous phenotype to day 161, which is associated with a steady decline in lung function and an increase in lung volume that accompanies an increase in airspace enlargement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination, this suggests that impaired cytokine secretion by professional APCs is not a contributing factor in CH25H‐deficient mice. Furthermore, recent evidence revealed that depletion of alveolar macrophages ameliorated elastase‐induced emphysema (Ueno et al , ), an iBALT‐independent emphysema mouse model (Dau et al , ; Sarker et al , ). Therefore, we utilized this model to demonstrate that loss of CH25H in macrophages did not impact upon emphysema development.…”
Section: Resultsmentioning
confidence: 99%
“…Lung function analysis were performed as previously reported 36 . Briefly, lung function was assessed by a forced maneuver system and a Fine-Pointe RC system (Buxco Research Systems; Wilmington, NC, USA).…”
Section: Methodsmentioning
confidence: 99%